Analysis of the Activities of Young Leaders in Enterprise Management - A. N. Kholiqulov; B. S. Burkxonov (PT ANTIS International Publisher, 2024)
In this article, the enterprise management system and the system of bodies all aspects of national importance, management training, re-training and improving their skills on the ongoing reforms in the country and keep in mind the analysis of their business activities.